The Influence of Dividend Policy, Investment Decisions and Capital Structure on Company Value (Empirical Study on LQ-45 Companies Listed on The Indonesian Stock Exchange for the 2018-2022 Period) - Sibarani, Silvia Paula Artha; Buchdadi, Agung Dharmawan; Widyastuti, Umi (Journal of Business and Behavioural Entrepreneurship, 2024)
The purpose of this study is to examine how Capital Structure, Investment Decisions, and Dividend Policy affect the value of LQ-45 firms listed on the Indonesia Stock Exchange between 2018 and 2022. A quantitative methodology is employed, utilizing documented evidence from literature, research publications from the past, and firm financial records. Purposive sampling was used to choose the sample. The study's findings demonstrate that, either in part or all at once, Capital Structure, Investment Decisions, and Dividend Policy do not significantly affect a company's value. External variables that have a greater influence on investor views, such as global market dynamics, regulatory changes, and macroeconomic conditions, might be the reason for this insignificance. The traditional financial theory tenet that capital structure, investment choices, and dividend policy affect business value is called into question by this study. Practically speaking, in an attempt to boost firm value, management is encouraged to take into account additional elements including market strategy, operational performance, and innovation. A more thorough and in-depth investigation is required to determine the actual determinants of firm value.